Hurricanes and storms - Twist, Clint (New York : Dillon Press, 1992)
Describes the characteristics of hurricanes and other kinds of storms, the damage they may cause, and possible protective measures.
Includes index.
Keywords: Hurricanes; Storms; Hurricanes; Storms